Zadek’s Osteotomy for Refractory Haglund Deformity: A Prospective Clinical and Radiological Evaluation with Surgical Technique and Outcomes - Dr Mithlesh Kumar Meena; Dr Vishwa Rewal; Dr. Vishal Ahke (PAIN, JOINTS, SPINE, 2026)
Background: Haglund deformity is a bony prominence of the posterosuperior calcaneus that causes mechanical irritation of adjacent soft tissues, most notably on the retrocalcaneal bursa and the Achilles tendon insertion, resulting in Haglund syndrome. The first line management is conservative but frequently insufficient in patients with severe symptoms and other management concerns due to vicinity to Achilles tendon. Zadek’s osteotomy is a biomechanical correction that preserves Achilles tendon insertion, addressing the underlying pathology while minimizing complications. This study aims to evaluate the clinical and radiological outcomes of Zadek’s osteotomy in patients with refractory Haglund deformity and retrocalcaneal bursitis.Methods: A prospective cohort of twelve patients with Haglund deformity unresponsive to at least six months of conservative treatment underwent Zadek’s osteotomy. Pre- and postoperative assessments included Visual Analog Scale (VAS) for pain, functional outcomes, radiographic measurements (Fowler-Philip angle, calcaneal pitch), and complications. The outcome was evaluated in patients during subsequent six months follow up.Results: Mean VAS improved significantly from 7.6 ± 0.8 preoperatively to 2.1 ± 0.7 at six months (p < 0.001). Among the participants, ten patients achieved excellent functional scores and two had good outcomes. Radiographs demonstrated significant reduction in the calcaneal prominence and Fowler-Philip angle. There were no major complications; one patient had transient lateral foot numbness which resolved in due course. No Achilles tendon ruptures or non-unions were observed.Conclusion: Zadek’s osteotomy is an effective and safe surgical intervention for refractory Haglund deformity, providing significant pain relief and functional improvement while preserving the Achilles tendon. It represents a biomechanically sound alternative to traditional resection procedures.